The Foster-Hart measure of riskiness for general gambles - Tobias Hellmann; Frank Riedel (Theoretical Economics, 2015)
Foster and Hart propose a measure of riskiness for discrete random variables. Their defining equation has no solution for many common continuous distributions. We show how to extend consistently the definition of riskiness to continuous random variables. For many continuous random variables, the risk measure is equal to the worst–case risk measure, i.e. the maximal possible loss incurred by that gamble. For many discrete gambles with a large number of values, the Foster–Hart riskiness is close to the maximal loss. We give a simple characterization of gambles whose riskiness is or is close to the maximal loss.
Keywords: D81; G11; 330; Risk measures; operational; bankruptcy; continuous random variable